Effects of government spending on economic growth, poverty and institutional quality in Asian countries - Liew, Chung Yee (2017)
Governments in developing and less developed Asian countries implemented large fiscal stimulus packages to cushion the shocks of global economic crisis. Nevertheless, the spending is unsustainable, the government spent more than receipts for many years. This study examined the effect of government spending on economic development in developing and less developed Asian countries from 1970 to 2013. Dynamic panel approach and Generalised Method of Moments (GMM) estimators were applied. This study first investigated the effect of government spending on economic growth in the existence of the spending threshold. The results suggest that current period government spending is significant and negative determinant of economic growth while one period lagged government spending is significant and positive determinant of economic growth. Threshold analysis suggests that Asian countries have been overspending and government spending is a significant and negative determinant of economic growth when government spending level is above the threshold value. For future growth, government spending should be results orientated and come with budget sustainability targeting. Next, this study investigated the effect of institutional quality on the effect of government spending on economic growth. The presence of institutional quality as a set of conditional variables is impact positively on the effect of government spending and economic growth nexus. The results suggest that higher institutional quality can offset the negative effect of government spending and generate growth-enhancing effect to economic growth. Finally, this study analysed the impact of government spending in eliminating poverty. The results in this study suggest that government spending does not reduce poverty but increases the cost to reduce poverty. Equality in distribution plays an important role because further analysis found that countries with more equality in income distribution leads to more equality in the distribution of government resources, and poverty reduction is more likely to meet the target. Besides, government spending in education and public health is also significant in reducing the poverty rate. Government spending is important to protect the vulnerable poor households before they benefit from the more long-term policies and strategies. However, the spending must not be anti-poor.